2022
DOI: 10.1186/s12936-022-04424-y
|View full text |Cite
|
Sign up to set email alerts
|

Malaria in Angola: recent progress, challenges and future opportunities using parasite demography studies

Abstract: Over the past two decades, a considerable expansion of malaria interventions has occurred at the national level in Angola, together with cross-border initiatives and regional efforts in southern Africa. Currently, Angola aims to consolidate malaria control and to accelerate the transition from control to pre-elimination, along with other country members of the Elimination 8 initiative. However, the tremendous heterogeneity in malaria prevalence among Angolan provinces, as well as internal population movements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…In 2021, the re-emergence of DENV, CHIKV, and ZIKV was established via PCR/sequencing using primers targeting the envelope of dengue virus serotype 1 (1485 bp). The updated entomological studies in both urban [ 109 , 110 ] and sylvan environments [ 111 ] showed high density and species richness of Aedes mosquito vectors in Gabon. Another interesting finding in Gabon was that which identified genes underlying specific resistance of DENV-1 and DENV-3 in Ae.…”
Section: Resultsmentioning
confidence: 99%
“…In 2021, the re-emergence of DENV, CHIKV, and ZIKV was established via PCR/sequencing using primers targeting the envelope of dengue virus serotype 1 (1485 bp). The updated entomological studies in both urban [ 109 , 110 ] and sylvan environments [ 111 ] showed high density and species richness of Aedes mosquito vectors in Gabon. Another interesting finding in Gabon was that which identified genes underlying specific resistance of DENV-1 and DENV-3 in Ae.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, molecular methods, such as polymerase chain reaction (PCR) assays, have been developed to detect kdr mutations, enabling the assessment of the frequency and distribution of these resistance-associated mutations in field populations [ 15 ]. Despite the crucial role of vector control in reducing malaria transmission, little published evidence on Angola malaria vector abundance, behaviour, and insecticide susceptibility has been published in the past 20 years [ 16 20 ]. This study aimed to describe the local populations of Anopheles mosquito species in two districts of Benguela, with a focus on characterising the vector abundance, behaviour, and insecticide susceptibility of these populations.…”
Section: Introductionmentioning
confidence: 99%
“…Malaria is a vector-borne disease caused by Plasmodium protozoa and transmitted through the bite of infected female mosquitoes from the genus Anopheles [ 1 ]. Of more than 120 Plasmodium species infecting mammals, birds, and reptiles, only six are known to infect humans: Plasmodium falciparum , P. vivax , P. malariae , P. ovale curtisi, P. ovale wallikeri and P. knowlesi [ 2 ].…”
Section: Introductionmentioning
confidence: 99%